As Competências do Professor de Educação Física na Pós-modernidade - Eunice Helena Tamiosso Vega (Universidade Federal do Rio Grande do Sul, 2002)
This article, resulting from the dissertation of Master Degree in Education submitted to the Catholic University of Rio Grande do Sul (PUCRS) in 2002, presents the competences of the physical-education teachers in the post-modernity. This research began after semi-structured interviews applied to students from two different university schools - a public and aprivateone- allowingtheapproachtotheserealities. Personal, professionalandsocialcompe-tencearose from the analysis of these interviews, integrating a wider study including the educational theories. The research conclusions lead to a critical evaluation of the basic competences included in a set of actions expressingthecurentmeaningofPhysicalEducation withing the educational and social context.